Exploration of Antifungal Tests Based on Δ-Guaiene From Subang Patchouli Oil - Rahmawati, Rahmi; Nurjanah, Sarifah; Rialita, Tita; Mardawati, Efri; Filianty, Fitry (CV. Inara, 2025)
Guaiene is a derivative compound produced as a byproduct in the production of patchouli alcohol from patchouli oil (Pogostemon cablin Benth.). This study aims to evaluate the antifungal activity of δ-guaiene extracted from patchouli oil originating from Subang against four types of skin pathogenic fungi: Aspergillus niger, Candida albicans, Microsporum gypseum, and Trichophyton mentagrophytes. The method used was a laboratory experiment, with the main parameters observed including Inhibition Zone Diameter (IZD), Minimum Inhibitory Concentration (MIC), and Minimum Fungicidal Concentration (MFC). The results showed that δ-guaiene inhibited the growth of C. albicans at a concentration of 40%, with an IZD of 0.15 mm. Against A. niger, the compound demonstrated an inhibition zone of 1.4 mm at a 20% concentration and had an MFC of 20%. For T. mentagrophytes, an IZD of 0.4 mm was observed, with both MIC and MFC at 20%. Activity against gypseum showed an IZD of 0.25 mm, with MIC and MFC also at 20%. These findings suggest that δ-guaiene from patchouli oil has potential as a candidate antifungal agent derived from local resources, supporting the development of natural bioactive compounds and sustainability.